Clinical features of usual interstitial pneumonia with anti‐neutrophil cytoplasmic antibody in comparison with idiopathic pulmonary fibrosis. Issue 5 (19th March 2016) - Hosoda, Chiaki; Baba, Tomohisa; Hagiwara, Eri; Ito, Hiroyuki; Matsuo, Norikazu; Kitamura, Hideya; Iwasawa, Tae; Okudela, Koji; Takemura, Tamiko; Ogura, Takashi
Abstract: Background and objective: Myeloperoxidase anti‐neutrophil cytoplasmic antibody (MPO‐ANCA) is occasionally positive in patients with usual interstitial pneumonia (UIP). However, the differences from idiopathic pulmonary fibrosis (IPF/UIP) have not been well documented. We aimed to clarify the clinical, radiological and pathological features of UIP associated with MPO‐ANCA (ANCA/UIP). Methods: We retrospectively reviewed the medical records of 12 consecutive ANCA/UIP patients not manifesting microscopic polyangiitis and 108 IPF/UIP patients with no autoantibodies, both diagnosed by surgical lung biopsy. Results: There was no significant difference in clinical background, laboratory results and pulmonary function tests between ANCA/UIP patients and IPF/UIP patients except for the percentage of bronchoalveolar lavage neutrophils. HRCT showed subpleural reticulation in both groups. Increased attenuation around honeycombing and cysts was significantly observed in ANCA/UIP. Pathologically, ANCA/UIP had more prominent inflammatory cell infiltration, lymphoid follicles with germinal centres and cellular bronchiolitis. During the disease course, three of 12 patients (25%) developed microscopic polyangiitis. Immunosuppressive treatment tended to be more effective in ANCA/UIP patients, and the survival time in ANCA/UIP patients tended to be longer than those with IPF/UIP. Conclusion: ANCA/UIP may be distinguishable from IPF/UIP with a combination of HRCT findings of increased attenuation around honeycombing and cysts and some of the characteristic pathological findings. In contrast to IPF/UIP, immunosuppressive treatment could be a therapeutic option for ANCA/UIP. Abstract : This is the first study to report on a direct comparison of pathologically proven usual interstitial pneumonia associated with MPO‐ANCA (ANCA/UIP) and idiopathic pulmonary fibrosis (IPF). This study shows some radiological and pathological characteristics and better responsiveness to immunosuppressive therapy in ANCA/UIP compared with IPF.